2020
DOI: 10.1093/applin/amaa037
|View full text |Cite
|
Sign up to set email alerts
|

Equity in Bilingual Education: Socioeconomic Status and Content and Language Integrated Learning in Monolingual Southern Europe

Abstract: Previous research has raised concerns that equity may be compromised in content and language integrated learning (CLIL) education, creating schisms in otherwise fairly egalitarian education systems. In Andalusia (southern Spain), where bilingual education has expanded, this article aims to analyze the difference between CLIL bilingual education and traditional monolingual education in terms of student equity indicators. A sample of over 3,800 students representing the four socioeconomic status (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 31 publications
1
12
0
4
Order By: Relevance
“…The findings discussed here should pave the way for future large-scale, cross-sectional analyses aimed at testing their generalizability. Nevertheless, results coincide with and complement those obtained in Lorenzo et al (2019) and Lorenzo et al (2020), which did target significance levels, the latter having a sample of over 3,800 students.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings discussed here should pave the way for future large-scale, cross-sectional analyses aimed at testing their generalizability. Nevertheless, results coincide with and complement those obtained in Lorenzo et al (2019) and Lorenzo et al (2020), which did target significance levels, the latter having a sample of over 3,800 students.…”
Section: Discussionsupporting
confidence: 86%
“…A series of studies conducted by the authors in the field of CLIL in Europe precede the present research (Lorenzo, Casal & Moore, 2010;Pérez, Lorenzo & Pavón, 2016;Lorenzo et al, 2019;Lorenzo, Granados & Rico, 2020). Some of these studies addressed issues like the description of incidental learning and positive transfer between L1 and L2, the benefits of CLIL over monolingual education, and the cooperation of linguist experts and content teachers for curriculum organisation and materials design.…”
Section: Introductionmentioning
confidence: 95%
“…CLIL is sometimes disputed to be selective and lack egalitarianism (e.g., Bruton 2015;Cenoz et al, 2014;de Dios Martínez Agudo, 2020;Lorenzo et al, 2021). In Sweden education is free of charge and the CLIL schools in this study are all municipality upper secondary schools to which any student can apply.…”
Section: Clil In Swedenmentioning
confidence: 94%
“…This is also in line with the aforementioned parent-investment model, as the students in the EFL contexts, such as in Indonesia, need familial support to access to English language education (Lamb & Coleman, 2008). This is due to the cost the students must afford in order to get into English courses (Lamb & Coleman), cram schools (Liu, 2020), or even EMI programs (Lorenzo et al, 2021), which could incur more expenditure than regular tuition. Some studies have shown that SES is significantly related to English proficiency; students with higher SES outperformed those with low SES in a Spanish bilingual school (Lorenzo et al, 2021) and also in German EMI and non-EMI schools (Trebits et al, 2021) and in the Philippines (Serquina & Batang, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%